PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF HELICOBACTER PYLORI ISOLATES FROM GASTRIC BIOPSIES OF PATIENTS IN TERTIARY CARE HOSPITAL - FATIMA , S; ULLAH , I; AYAZ , M; MALIK , K; SHAIEA , MNQ; YAN , X; HAN , L; ZHAO , L (Biological and Clinical Sciences Research Journal, 2024)
Worldwide, Helicobacter pylori is prevalent and is strongly associated with causing numerous digestive tract infections. Combination therapy for this pathogen includes a combination of antimicrobials such as amoxicillin, metronidazole, clarithromycin, levofloxacin, and proton pump inhibitors. Even though the present therapy is effective, treatment failure has been observed. This failure has been observed to be mainly due to point mutation, which in H. pylori is considered the primary developed resistance mechanism. This study investigated the prevalence and drug susceptibility of H. pylori in patients in Mufti Mehmood Memorial Teaching Hospital, Dera Ismail Khan, Pakistan, from 2016 to 2017. A total of 100 gastric biopsies of patients were included in our study. All the samples were cultured and identified by biochemical testing for H. pylori to determine the prevalence. The disk diffusion method was used for the determination of the susceptibility pattern. Among 100 patients, H. pylori strains were isolated from 52 (52%) patient samples. To metronidazole (MTZ), maximum number of isolates (69.23%) shows resistance. Resistance to other antibiotics was also detected, including clarithromycin (CLR; 50%) and amoxicillin (AML; 57.69%). Comparatively low resistance was observed to tetracycline (TET; 7.69%) and ciprofloxacin (CIP; 15.38%) by a few isolates in our study. These data suggest that metronidazole should be used among Pakistani patients in first-line therapy with caution and ciprofloxacin in association. The clinician must know their area’s resistance patterns when selecting an empiric antibiotic regimen for H. pylori.